The Dynamics of Extrasystolic Periods with Respect to Refractive Period in Mathematical Model of Parasystole - Skučas, M.; Grigaliūnienė, I.; Eidukas, D.; Labrencas, R.; Eidukas, D. (Elektronika ir Elektrotechnika, 2006)
To verify the hypothesis that many frequent extrasystoles (ES) can appeare throug the competition of ectopic excitation with pulses of sinus node, we created the mathematical computer-based model of parasystolic arrhythmias, taking into account possible variability of pulses of these pacemakers. We investigated the conditions of appearance of recurrent ES and subsequent dynamics of the ES dependent on the duration of refractory period (Tref) in this model. , approaching to T= T/2 (TWe established that the duration of the Trefref ss – shorter periods of excitation pulses), predetermine the moment of appearance of the recurrent ES. The duration of Tref predetermined shortening of pre-extrasystolic periods. Groupes of ES remain as long as the duration of T remains close to T/2. Changes in the length of T trigger appearance of sporadic ES when Trefsrefref = T/2, and these remain as long as T